La création d’une nouvelle filière dans le cadre de la requalification de friches industrielles à grande échelle : les paysages productifs - Julien Lahaie (Projets de Paysage)
An industrial platform located in the south of the Lyons metropolis, La vallée chimique (Chemical Valley) is a singular landscape at the entrance to the city. Deeply marked by human intervention (in the Petrolocene era), the different parts of this landscape have been reinvented in the course of the past industrial activities of the big petrochemical firms and of regulatory changes. This article focuses on the contemporary context marked by a resumption in the development of this large industrial platform by the local authorities (principally the Lyon metropolis). After reviewing the historical context and the emergence of the industrial landscapes, the article deals with major current changes, notably via a participative approach developed within the framework of the call for projects, "L'appel des 30 ! Lyon vallée de la chimie".